The potential application of sulfonated polystyrene (SPS) from recycled styrofoam in the reduction of heavy metals -Ba+2, Cd+2, Cr+3, Pb+2 and Ni+2 in wastewater - Manalac, Sharon M. (2007)
This study investigates the potential of using sulfonated polystyrene (SPS) from recycled styrofoam in the reduction of heavy metals - Ba+2, Cd+2, Cr+3, Pb+2 and Ni+2, in wastewater.